Preliminary design of control rods in the single-fluid double-zone thorium molten salt reactor (SD-TMSR). (March 2021) - Ashraf, O.; Rykhlevskii, Andrei; Tikhomirov, G.V.; Huff, Kathryn D.
Highlights: A reliable safety system based on control rods has been introduced in the SD-TMSR. Three different initial fissile loadings are considered. Six different absorbing materials have been investigated. Integral and differential control rod worth, SDM, and shadowing effects at steady-state were calculated. Abstract: Recent studies on Molten Salt Reactors (MSRs) showed that the excess reactivity at the beginning of the operation is large for many fueling strategies and must be compensated by a reactivity control system. The current work introduces a reliable safety system based on control rods in addition to the online feed system reactivity control in the Single-fluid Double-zone Thorium-based Molten Salt Reactor (SD-TMSR). Three different initial fissile loadings are considered: 233 U, reactor-grade Pu, and transuranic (TRU) elements as a startup fuel. We applied six different absorbing materials to investigate the main operational and safety parameters in the SD-TMSR: natural B4 C, enriched B4 C with 90% 10 B, HfB2, HfH1.62, Eu2 O3, and Gd2 O3 . The present work focuses on control rod design, integral and differential control rod worth, shutdown margin, and shadowing effects at steady-state. We employed the SERPENT-2 Monte-Carlo code to calculate the reactivity worth and analyze the performance of the reactivity control system. We showed that 233 U and reactor-grade Pu startup cores maintain adequate shutdown margin with all considered absorbers. Finally, this paper proposes a design of control rod clusters that compensate the excess reactivity of the SD-TMSR loaded with different initial fissile material.